Vegetable Cultivation Using Residents' Yard Land to Increase Food Security in Gelanggang Village, East Sakra District, East Lombok Regency - Kahar, Abdul; Hanani, Hulfiatun; Rizwan, Mohamad Rido; Juniarti, Juniarti; Yuliana, Yuliana; Fitri, Ruhil; Nabilah, Nabilah; Komalasari, Ulvi Intan; Fathan, Muhammad; Azhari, Rudi; Hikmawati, Hikmawati (Pascasarjana Universitas Mataram, 2024)
Gelanggang Village is one of the villages located in East Sakra District, East Lombok Regency, which has great potential in the agricultural sector and almost 90% of the people living in Gelanggang village work as farmers. However, other plants such as vegetables, which are one of the food necessities, are not widely planted and cultivated, because they are considered less productive for the community. Apart from that, the people of Gelanggang village also have large plots of land which are not utilized. The aim of the main KKN-PMD program activities in Gelanggang Village is to provide education regarding the use of residents' yards for cultivating vegetable crops and increasing the food security of the Gelanggang Village community. The stages in carrying out the main KKN-PMD work program activities in Gelanggang Village are the first stage sowing vegetable seeds, the second stage making Verticulture shelves and the last stage carrying out outreach. The result obtained from this activity is that by conducting outreach related to vegetable cultivation, this can provide education regarding the use of residents' yard land for cultivating vegetable plants. Apart from that, this outreach is also an effort to increase the food security of the Gelanggang village community